Effectiveness of Wood Vinegar from Torrefied Coconut Shells as an Eco-friendly Pesticide against Fall Armyworm (Spodoptera frugiperda J.E Smith) - Purnama Indra; Lestari Sri Dewi; Lidar Seprita; Mutamima Anisa; Suri Atika; Nelvia Nelvia; Malhat Farag M. (E3S Web of Conferences)
The instability in crop production caused by pest infestations, particularly by the fall armyworm (Spodoptera frugiperda J.E. Smith), poses significant challenges in agriculture. Conventional chemical pesticides, while effective, contribute to environmental degradation, pesticide residues in food products, and increased resistance among pest populations. As an alternative, this study explores the use of wood vinegar derived from torrefied coconut shells as a botanical pesticide for managing S. frugiperda infestations. An experimental design using a completely randomized layout was implemented, comprising five treatment concentrations (0%, 3%, 5%, 8%, and 10%) of wood vinegar in water, each replicated four times. A total of 200 third instar larvae of S. frugiperda were subjected to these treatments, with each experimental unit containing 10 larvae in individual plastic cups. Key parameters observed included initial mortality time, lethal time 50, overall mortality rate, and lethal concentration 50 and 95. The results demonstrated a significant impact of wood vinegar concentration on larval mortality. The 10% concentration yielded the highest efficacy, achieving an 80% mortality rate. Further analysis using Duncan’s multiple range test at a 5% significance level confirmed this concentration as optimal. The findings indicate that wood vinegar from torrefied coconut shells is a potent, ecofriendly alternative to chemical pesticides.